2019
DOI: 10.1177/0892705719832072
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of chemical modification on sugarcane bagasse mixed with polypropylene and recycle acrylonitrile butadiene rubber composite

Abstract: The goal of this research is to investigate the thermal, chemical, and tensile properties of chemical modification of sugarcane bagasse (SCB)-filled polypropylene (PP) and recycled acrylonitrile butadiene rubber (NBRr). The composites with different SCB loading (5, 15, and 30 per hundred resin) were prepared using a heated two-roll mill at temperature of 180°C.Thermal and the tensile properties of the modified SCB composite have shown improvement. The silane-treated composites have higher thermal stability com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
4
15
0
Order By: Relevance
“…Therefore, the mechanical strength improvement observed in the PP-Bagasse biocomposites could be related to the reinforcement effect of bagasse fibers in the PP and the crystallinity changes of the thermoplastic matrix. Similar results were reported by Zainal et al [ 21 ] on polypropylene-acrylonitrile butadiene rubber-modified bagasse biocomposites. They reported that the chemical treatment of bagasse fibers using silanes increases the nucleation density and the crystallinity degree (%) of the polymeric matrix.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, the mechanical strength improvement observed in the PP-Bagasse biocomposites could be related to the reinforcement effect of bagasse fibers in the PP and the crystallinity changes of the thermoplastic matrix. Similar results were reported by Zainal et al [ 21 ] on polypropylene-acrylonitrile butadiene rubber-modified bagasse biocomposites. They reported that the chemical treatment of bagasse fibers using silanes increases the nucleation density and the crystallinity degree (%) of the polymeric matrix.…”
Section: Resultssupporting
confidence: 91%
“…The scanning electronic microscopy gives valuable information about biocomposites morphological characterization. Several authors have made conclusions studying the fiber content (composition), the chemical treatment of natural fibers, and biocomposites reprocessing using SEM [ 12 , 20 , 21 , 44 ]. This technique, together with the performed rheological and dynamic mechanical characterization, could provide valuable evidence of the dispersion state of the fibers within the biocomposites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering Figure 7 b, it is observed that there were small decreases in relation to the Tm of PP-HDPE-CCF biocomposites compared to neat PP-HDPE blend. This thermal behavior has been already observed in several studies regarding biocomposites as PLA-Ramie [ 46 ] and PP-NBr-Bagasse fibers [ 47 ]. This decrease (albeit small), is due to the incompatibility between non-polar hydrophobic matrices and polar hydrophilic untreated CCF fiber which leads to poor interfacial properties and thus lowering the melting point.…”
Section: Resultssupporting
confidence: 73%
“…They concluded that injection molding process results in homogenous distribution of fibers and is free of blisters; however, the obtained composites did not present good flexural and tensile strengths while a moderate increase in flexural modulus was observed. Zainal et al prepared sugarcane bagasse/PP composite with weight fraction 5, 15, and 30 wt% using two‐roll mill mixer. The fibers were treated with 5 wt% NaOH and 5 wt% γ‐APS silane.…”
Section: Introductionmentioning
confidence: 99%